Efficacy and safety of SilverNovaTM skin cream as adjuvant to oral and topical antifungals in treatment of fungal skin infections - Talathi, Abhay; Jadhav, Avinash; Purohit, Sanjay; Mehta, Anirudh (International Journal of Research in Medical Sciences, 2023)
Background: To evaluate the efficacy and safety of SilverNovaTM skin cream, composed of SilverSol® (a patented colloidal nano silver technology from American Biotech Labs, USA) with other skin rejuvenators (coconut oil, vitamin E, and hyaluronic acid), as an adjuvant to topical and oral antifungals in the treatment of fungal skin infections like tinea and intertrigo. Methods: This prospective clinical study enrolled 80 patients with tinea corporis, tinea cruris, tinea manus, tinea pedis infections, and intertrigo. The patients were randomized to receive either SilverNovaTM skin cream and clotrimazole cream (n=40) or clotrimazole cream (n=40) alone applied topically as an adjuvant to oral antifungal therapy for 14 days. The primary endpoints were the reduction of clinical signs and symptoms of the infection at the end of the treatment and the proportion of patients with therapeutic cures. Results: SilverNovaTM skin cream exhibited better efficacy and safety than clotrimazole cream, though without reaching clinical significance at the end of the treatment. On the 14th day, there was an improvement in clinical signs and symptoms of fissuring/cracking, erythema, maceration, scaling, pruritus, and burning/stinging from baseline in patients with tinea infections, and intertrigo in both the treatment groups. A higher proportion of patients reported therapeutic cures at the end of the treatment, numerically better with SilverNovaTM skin cream group. No drug-related adverse events occurred. Conclusions: SilverNovaTM skin cream is effective and well tolerated as an adjuvant to topical and oral antifungals for the treatment of fungal skin infections like tinea and intertrigo.